(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
The text presents part of the artistic journey taken by the Teatro Del Carretto, from the city of Lucca, Italy. The author, its director, discusses some of the creative procedures used in 11 theatrical stagings, indicating the option for original dramatic resources, the use of masks and puppets and focuses mainly on the work of the actor. Concerning the later issue, it highlights multiple devices used by the cast such as the use of the grotesque, disguise, deformations, and the marionette-like behavior of the actor, to construct a universe of surpise and dream. Keywords: Theatrical staging. Creative process. Teatro Del Carretto.